2008
DOI: 10.1111/j.1365-2958.2008.06305.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and genetic validation of dihydrofolate reductase–thymidylate synthase as a drug target in African trypanosomes

Abstract: SummaryThe phenotypes of single-(SKO) and double-knockout (DKO) lines of dihydrofolate reductase-thymidylate synthase (DHFR-TS) of bloodstream Trypanosoma brucei were evaluated in vitro and in vivo. Growth of SKO in vitro is identical to wild-type (WT) cells, whereas DKO has an absolute requirement for thymidine. Removal of thymidine from the medium triggers growth arrest in S phase, associated with gross morphological changes, followed by cell death after 60 h. DKO is unable to infect mice, whereas the virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 58 publications
(111 reference statements)
6
103
0
Order By: Relevance
“…Animals were inspected daily for clinical signs of infection, and wet smears of tail blood were examined microscopically as appropriate. Parasitemia was determined using a Neubauer hemocytometer, as previously described, and infected mice were monitored for 30 days (34). Mice with parasitemia that exceeded 10 8 cells ml Ϫ1 were humanely killed, since prior experience indicated that animals would succumb to an overwhelming infection by the following day.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were inspected daily for clinical signs of infection, and wet smears of tail blood were examined microscopically as appropriate. Parasitemia was determined using a Neubauer hemocytometer, as previously described, and infected mice were monitored for 30 days (34). Mice with parasitemia that exceeded 10 8 cells ml Ϫ1 were humanely killed, since prior experience indicated that animals would succumb to an overwhelming infection by the following day.…”
Section: Methodsmentioning
confidence: 99%
“…has resulted in a highly restricted genomic repertoire, compensating for the absence of biosynthetic pathways by encoding transporters to sequester metabolites (including folate) from the environment (120,121). This enhanced biosynthetic capability may contribute to the higher reported vector competency of the G. morsitans host relative to G. brevipalpis (96)(97)(98)100), as trypanosomes necessitate exogenous folate for growth (122). Deeper investigation of this hypothesis is required.…”
Section: Understanding the Tsetse Holobiont For Enhanced Vector Controlmentioning
confidence: 99%
“…This issue is not limited to drug-induced perturbations, as studies of genetic manipulation for target validation may also be complicated by excess nutrient availability (17). Indeed, this "metabolite rescue" approach is often used intentionally to generate conditional gene knockouts or to confirm chemical or genetic enzyme inhibition (17,18). However, the use of a rich culture medium may unintentionally hinder drug discovery efforts that utilize phenotypic screening approaches, as demonstrated for dihydrofolate reductase (DHFR)-thymidylate synthase inhibitors, which demonstrated significant trypanocidal activity only when the medium was depleted of folic acid (17).…”
mentioning
confidence: 99%
“…Also, drug-induced metabolic perturbations can be easily masked by compensatory mechanisms if there are high metabolite concentrations available in the culture medium. This issue is not limited to drug-induced perturbations, as studies of genetic manipulation for target validation may also be complicated by excess nutrient availability (17). Indeed, this "metabolite rescue" approach is often used intentionally to generate conditional gene knockouts or to confirm chemical or genetic enzyme inhibition (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation